The Relevance of Multicultural Islamic Religious Education with Hassan Hanafi's Liberation Theology - Adi Wijaya (CV. Creative Tugu Pena, 2024)
This research discusses the importance of multicultural Islamic Religious Education (PAI) in Indonesia, which plays a role in overcoming social conflicts, intolerance and injustice that often arise in diverse societies. This education is in line with Law no. 20 of 2003 concerning the National Education System which emphasizes the importance of religious education in shaping the character of students. Multicultural PAI teaches the values ​​of tolerance, mutual respect and social justice. This approach is relevant to Hasan Hanafi's concept of liberation theology, which emphasizes liberation from all forms of oppression and justice for all humanity, as well as equality as the main principle in coexistence. This study uses the method literature study (library research) and figures related to the relevance of multicultural Islamic religious education to liberation theology. The findings of this research show that a multicultural approach in Islamic Religious Education, which is in line with Hassan Hanafi's liberation theology, can effectively overcome social problems such as intolerance and radicalism. As a result, these findings can form a younger generation that is more adaptive, appreciates diversity, and is active in fighting for social justice, thereby contributing to the creation of a more harmonious and peaceful Indonesian society.